PROSPECTIVE EVALUATION OF MEDIUM-TERM OUTCOMES OF PATIENTS UNDERGOING HYSTEROSCOPIC UTERINE SEPTUM RESECTION - Gülten Çirkin Tekeş (International Journal of Health Services Research and Policy, 2021)
Objectives: To retrospectively and prospectively investigate the pregnancy outcomes after hysteroscopy (H/S) for septum resection in patients detected to have a uterine septum after presenting with a history of recurrent pregnancy loss (RPL), diagnosis of secondary infertility or primary infertility. Methods: This study included 62 patients with infertility or a history of RPL who underwent hysteroscopic uterine septum resection. Patients who had uterine anomalies other than a uterine septum, such as submucous myoma, endometrial polyp were excluded. Those discharged home with a live infant after a uterine septum operation were compared based on certain variables, those who succeeded and those who failed were categorized into group 1 and group 2, respectively. The two groups were compared with regard to the total number of deliveries before and after the operation, total number of abortions, preterm and term deliveries, delivery methods, control hysterosalpingographies (HSG) and whether they were reoperated. Results: In our study, 25 (40%) patients were primary infertile, 37 (60%) had secondary infertility or a history of RPL. Hysteroscopic septum resection was performed under general anesthesia in 61 and spinal anesthesia in 1 of these patients. Of the patients who were postoperatively discharged home with a live infant, 8 (26.7%) were determined to be primary infertile and 22 (73.3%) to have secondary infertility or a history of RPL. The rate of discharge with a live infant was determined as 76.9% among patients who conceived. The success rate of Group 1 patients, who were secondary infertile or had history of RPL, was significantly higher compared to patients who were primary infertile. Conclusions: Hysteroscopic uterine septum resection is a method with an easy application and high effectiveness. The success of the operation is particularly higher in patients who have a history of RPL or are secondary infertile compared with patients who are primary infertile.